Compound Hot and Dry Events in Europe: Variability and Large-Scale Drivers - Ionita, Monica; Caldarescu, Diana E.; Nagavciuc, Viorica (Frontiers in Climate, 2021)
An important aspect of inevitable surprises, for the climate system, is the potential of occurrence of compound extreme events. These can be events that occur at the same time over the same geographic location or at multiple locations within a given country or around the world. In this study, we investigate the spatio-temporal variability of summer compound hot and dry (CHD) events at European level and we quantify the relationship between the occurrence of CHDs and the large-scale atmospheric circulation. Here we show that summer 1955 stands out as the year with the largest spatial extent characterized by hot and dry conditions (~21.2% at European level), followed by 2015 (~20.3%), 1959 (~19.4%) and 1950 (~16.9%). By employing an Empirical Orthogonal Function (EOF) analysis we show that there are three preferred centers of action of CHDs over Europe: Fennoscandia, the central part of Europe, and the south-eastern part of Europe. Overall, hot and dry summers are, in general, associated with persistent high-pressure systems over the regions affected by CHDs, which in turn reduces the zonal flow and diverts the storm tracks southward. The high-pressure systems associated with each mode of variability largely suppresses ascending motions, reduces water vapor condensation and precipitation formation, leading to drought conditions below this atmospheric system. This study may help improve our understanding of the spatio-temporal variability of hot and dry summers, at European level, as well as their driving mechanisms.